Effect of different pollination schemes on the fruit morphometric characteristic of Vanilla planifolia Jacks. - Zelzin Eréndira Fernández-Villa; Brandon Giovanni Cervantes Rodríguez; Lourdes Georgina Iglesias-Andreu (Ornamental Horticulture, 2025)
Vanilla planifolia Jacks. is an orchid of great economic interest, classified as endangered. The limited genetic variation of this species has been primarily attributed to its clonal propagation. Genetic improvement through pollination schemes allows for improving the characteristics of fruits, seeds, and seedlings, increasing resistance to biotic and abiotic stress. Therefore, it was proposed to develop the present work to evaluate the effect of three pollination schemes at different times on the morphometric characteristics of the fruit. 65 flowers in the anthesis phase were randomly selected and subjected to the following treatments: 1) natural pollination with emasculated flowers, 2) manual pollination by autogamy, and 3) geitonogamy, in a vanilla plantation located in Mesa de Guadalupe, Veracruz, Mexico. The percentage of set and retained fruits, growth dynamics (length and diameter), weight, and shape index of the fruits were evaluated for each pollination scheme and on different days after pollination (DAP). Fruit formation by natural pollination was not observed, which shows the absence of apomixis and fertilization by any pollinating agent in this vanilla plantation. No differences were observed in the set and retention of fruits obtained by autogamy and geitonogamy. The growth dynamics show that the fruits reach their maximum length at 40 DAP for both pollination schemes. Greater length, shape index, and weight were observed in the fruits obtained by geitonogamy at 40 DAP. These results show that inbreeding has no apparent effects on capsule production in V. planifolia but does influence its morphometric characteristics.